Menekan Laju Global Warming Melalui “Trustation” sebagai Bank Sampah Di Lingkungan Universitas - Hardiyanti, Retno Ayu; Bratanegara, Aldini Safarach; Nur, Muhammad; Fitriyani, Anindyta; Nurhalizah, Siti; Nurhalimah, Anisa; Desiany, Mia (Program Studi Magister Manajemen Lingkungan, 2024)
Waste banks are a potential solution for managing waste in tertiary institutions, and TRUSTATION (Trust Your Trash to Our Station) is a waste bank planned to operate within the Indonesian University of Education (UPI) as a revolution in the process of overcoming waste problems. To realize TRUSTATION and show that UPI is taking waste problems seriously, an analysis of the waste management condition within UPI is needed. This research aims to explain the waste management system at UPI, the response of UPI residents to waste management, and the idea of establishing a waste bank. The study uses a mixed-method approach with data collection techniques including interviews, surveys, and literature studies. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Results of the study show that waste management at UPI still relies on sorting and processing at the TPS level. UPI residents choose to hand over their waste to the waste management, but the absence of waste processing facilities on campus or around their residence is a significant obstacle, causing waste to remain mixed at the TPS. Therefore, UPI residents support the establishment of a waste bank within UPI.